1998
DOI: 10.1038/eye.1998.248
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness in the diagnosis of sarcoidosis: The conjunctival biopsy

Abstract: Purpose Sarcoidosis is a multi-system disease that often affects ocular structures. The definitive diagnosis of sarcoidosis requires tissue biopsy for confirmation. Conjunctival biopsy is a simple and relatively inexpensive diagnostic tool. This study was undertaken to determine the utility and cost of conjunctival biopsy for the diagnosis of sarcoidosis compared with other diagnostic biopsy sites. Pulmonary involvement is the most common clinical manifestation of the disease. Transbronchial and mediastinal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In the literature, some institutions performed 5 to 6 serial sections at three levels [ 1 ] whereas others performed 10 serial sections at 6 different levels for a total of 60 sections [ 2 ]. No studies to date have evaluated the effect of number of serial sections on conjunctival biopsy yield, although the importance of careful sectioning has been previously emphasized [ 1 , 5 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, some institutions performed 5 to 6 serial sections at three levels [ 1 ] whereas others performed 10 serial sections at 6 different levels for a total of 60 sections [ 2 ]. No studies to date have evaluated the effect of number of serial sections on conjunctival biopsy yield, although the importance of careful sectioning has been previously emphasized [ 1 , 5 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of granulomas with conjunctival biopsy using careful sectioning technique approaches the yield obtained from other tissue sites [ 16 , 17 ], especially when conjunctival pathology such as nodules, follicles, or fibrous scarring is present [ 4 , 12 , 18 ]. No false positives have been reported in previous studies [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Bilateral biopsy is recommended because abnormalities can often be seen only on one side. However, a more recent retrospective study evaluating the use of conjunctival biopsy in 440 suspected cases of neurosarcoidosis (the diagnosis had to be included as a surgical indication or in the neurology clinic notes) reported only a 3% (13 of 440) rate of abnormalities consistent with ocular sarcoidosis, of which 1% (4 of 440) was ultimately found to have another cause for the neurologic symptoms.…”
Section: Conjunctival Biopsymentioning
confidence: 99%
“…In rare cases, conjunctival biopsy may demonstrate granulomas; however, the routine use of this approach has not been established yet. While some studies suggested clinical utility with findings consistent with sarcoidosis in up to 55% of cases even in the absence of ocular disease, 81,82 a more recent study of 440 suspected cases of neurosarcoidosis reported only 13 of the 440 (3%) with an abnormal conjunctival biopsy. 83 Treatment for neurosarcoidosis is largely based on retrospective studies and expert opinion due to the lack of randomized clinical trials.…”
Section: Sarcoidosismentioning
confidence: 99%